Catching the Red Dragon: Motives, Strategies and Challenges of Italian Investment in China - Tomaselli, Federica (2015)
China has been the major destination of Foreign Direct Investment for the past 20 years and its miraculous economic achievements have become a popular topic among scholars and business people. Nowadays going to China is a must and it constitutes an opportunity that cannot be missed. In this context Italian companies have also been attracted by the endowment of cheap labour and tax incentives offered by the red dragon, however, as late comers, they weren’t capable of taking full advantage of the great opportunities presented by the Middle Kingdom. The flow of FDI in the 21st century has been greatly disappointing and almost insignificant compared to other European members. This paper aims at investigating the motives, strategies and challenges of Italian firms in China. It also points out the underlining changes experienced by Italian companies over the years. The research conducted in this thesis has adopted a qualitative interview approach. The sample population includes 15 Italian firms, mainly small and medium enterprises of heterogeneous size. Results overall showed similarities to previous research however, it expanded on by revealing new modes, strategies and challenges of Italian enterprises in China.